2023
DOI: 10.1086/723111
|View full text |Cite
|
Sign up to set email alerts
|

Peer Gender and Schooling: Evidence from Ethiopia

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
3
5
0
Order By: Relevance
“…The systematic reviews by Bahji and Stephenson (2019), Wilson and Rhee (2022) and Athanassiou et al (2022) cited earlier, as well as two observational studies (Vignault et al, 2021;Wang et al, 2022), found that legalisation of recreational use was followed by a rise in a range of mental health-related issues. These include higher numbers In contrast, a 'difference-in-differences' study conducted in the US (from 1993 to 2019) found that although cannabis legalisation resulted in increased cannabis use, it did not find evidence for any effect on measures of mental health distress (Borbely et al, 2022).…”
Section: Impacts On the General Populationmentioning
confidence: 87%
See 1 more Smart Citation
“…The systematic reviews by Bahji and Stephenson (2019), Wilson and Rhee (2022) and Athanassiou et al (2022) cited earlier, as well as two observational studies (Vignault et al, 2021;Wang et al, 2022), found that legalisation of recreational use was followed by a rise in a range of mental health-related issues. These include higher numbers In contrast, a 'difference-in-differences' study conducted in the US (from 1993 to 2019) found that although cannabis legalisation resulted in increased cannabis use, it did not find evidence for any effect on measures of mental health distress (Borbely et al, 2022).…”
Section: Impacts On the General Populationmentioning
confidence: 87%
“…Some countries have followed a more staged approach than others, where legalisation of recreational use was preceded by different levels and/or forms of decriminalization or waves of policy reform. For example, the US began its legalisation journey in 1996 when California first legalised medicinal use (Borbely et al, 2022). By 2021, 25 years later, the majority of states had legalised medicinal use and 17 states, and the District of Columbia had legalised recreational cannabis (Wilson & Rhee, 2022).…”
Section: International C Annab Is P Olic Y Reform and Its Driving Fac...mentioning
confidence: 99%
“…My findings speak specifically to treatment admissions and should not be conflated with improving or declining mental health as the evidence on the effects of RMLs on mental health remains mixed. For instance, Borbely et al (2022) find some evidence of poorer self-reported mental health among younger individuals residing in RML states but improvements among elderly individuals. Wang et al (2022) find no effect on emergency department (ED) visits for schizophrenia but an increase in psychosis ED visits.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies find a weak relationship between state marijuana laws and mental health or suicide after accounting for confounding factors (Anderson et al, 2014;Leung, 2019). Conversely, recent studies find an ad-verse effect of RMLs on mental health, particularly for younger individuals (Borbely et al, 2022;Sturman, 2022). Wang et al (2022) finds that increasing the number of dispensaries in an RML state leads to increases in psychosis-related ED visits.…”
Section: Orcidmentioning
confidence: 97%
“…This study integrates two streams of emerging cannabis economics literature by using refined geographic measures to examine cannabis availability's effects on mental health. Three prior studies (Borbely et al 2022;Sabia, Swigert, and Young 2017;Nicholas and Maclean 2019), to our knowledge, have examined cannabis legalization's effects on mental health, though they rely on state variation in cannabis laws to identify cannabis availability's effects rather than substate variation in dispensary variation, as we do. Other recent studies have used sub-state geographic variation in dispensary availability to examine other health outcomes (Wang et al 2022;Smith 2020;Conyers and Ayres 2020;Ambrose, Cowan, and Rosenman 2021).…”
Section: Introductionmentioning
confidence: 99%